Can music improve sleep quality in adults with primary insomnia? A systematic review and network meta-analysis. (January 2018) - Feng, Fan; Zhang, Yingshi; Hou, Jun; Cai, Jiayi; Jiang, Qiyu; Li, Xiaojuan; Zhao, Qingchun; Li, Bo-an
Abstract: Background: Primary insomnia is one of the most common issues for adults. However, whether to use music intervention as a non-pharmacological method of treatment, as well as which treatment should be preferred, is still a matter of controversy. Therefore, we aimed to compare and rank music interventions and no-music controls for primary insomnia patients. Methods: A network meta-analysis was used to identify evidence from relevant clinical trials. We searched PubMed, Embase, the Cochrane Library, and the China National Knowledge Infrastructure Library for publications up to May 2017, pertaining to music intervention for primary insomnia patients. The prespecified primary outcome was sleep quality (scored by the PSQI and overall), and the secondary outcomes were sleep onset latency and sleep efficiency. We did pairwise meta-analyses using the random-effects model, later completing the random-effects network meta-analyses. The study was registered with PROSPERO, number CRD42017064750. Results: We deemed 20 trials to be eligible, involving 1339 patients and 12 intervention arms. For PSQI scores, all intervention arms were statistically more effective than the usual care, with patients ranking listening to music as the best means of intervention (SMD: −0.61, 95%CrI: −1.01 to −0.20). For overall sleep quality, only music-associated relaxation was statistically more effective than the patients' usual care (−0.28, −0.48 to −0.08). In terms of sleep onset latency, music-associated relaxation and listening to music had significant advantages (−0.26, −0.64 to −0.09, and −0.28, −0.53 to −0.02); listening to music and music with exercise displayed a tendency to improve sleep efficiency. Conclusions: When considering the efficacy, music intervention seemed to offer clear advantages for adults with primary insomnia. Listening to music and music-associated relaxation are probably the best options to consider in the application of music intervention.